Association of Plaque Morphology With Stroke Mechanism in Patients With Symptomatic Posterior Circulation ICAD. (13th December 2022) - Song, Xiaoyan; Li, Shuang; Du, Heng; Hu, Qimin; Zhou, Li; Zhao, Jinglong; Gu, Yue; Hu, Yiming; Lu, Haiyan; Wang, Guodong; Chen, Xiangyan; Wang, Qiaoshu
Abstract : Background and Objectives: Although the main mechanisms of stroke in patients with intracranial atherosclerotic disease (ICAD)—perforating artery occlusion (PAO) and artery-to-artery embolism (AAE)—have been identified and described, relatively little is known about the morphology of the symptomatic plaques and how they differ between these 2 mechanisms. Methods: We prospectively recruited patients with acute ischemic stroke in the posterior circulation that was attributable to ICAD. Fifty-one eligible patients were enrolled and underwent magnetic resonance imaging before being assigned to the PAO or AAE group according to probable stroke mechanism. Plaque morphological properties including plaque length, lumen area, outer wall area, plaque burden, plaque surface irregularity, vessel wall remodeling, and plaque enhancement were assessed using high-resolution MRI. Plaque morphological parameters of both PAO and AAE groups were compared using nonparametric tests. A binary logistic regression model was used to identify independent predictors while a receiver operating characteristic curve tested the sensitivity and specificity of the model. Results: Among patients who met the imaging eligibility criteria, 38 (74.5%) had PAO and 13 (25.5%) had AAE. Plaque length was shorter (6.39 interquartile range [IQR, 5.18–7.7]1 mm vs 10.90 [IQR, 8.18–11.85] mm, p < 0.01) in patients with PAO. Plaque burden was lower in PAO group (78.00 [IQR, 71.94–86.35] % vs 86.37 [IQR, 82.24–93.04] %, p = 0.04). The proportion of patients with plaque surface irregularity was higher in patients with AAE than in patients with PAO (19/38, 50.00% vs 12/13, 92.30%, p = 0.008). Plaque length was significantly associated with the PAO mechanism (adjusted OR 0.57, 95% CI, 0.41–0.79). Discussion: Intracranial atherosclerotic plaque morphology differs between patients with PAO and those with AAE. Plaque with shorter length, lower plaque burden, and regular surface is more likely to cause PAO.